Trends in marine fish catches at Pattani Fishery Port (1999-2003) - Wanchamai Karntanut; Premwadee Komontree; Phattrawan Tongkumchum (Songklanakarin Journal of Science and Technology (SJST), 2006)
This study aims to develop statistical models for forecasting the quantity of the various types of marine fish landed at Pattani Fishery Port, allowing for trend and seasonality, using official data during 1999-2003. The data comprise daily and monthly totals by weight for eight types of fish (mackerel, other food fish, squid, scads, trash fish, shrimp, lobster and crab). The statistical methods are one-way analysis of variance, multiple linear regression and time series forecasting using trend and seasonal models. It is found that mackerel, other food fish and squid catches tend to decrease, whereas the catches of scads tend to increase, and trash fish catches have no detectable trend up or down. Shrimp and lobster tend to decrease exponentially, and the trend of crab catch is constant. This study raises questions about the ecological and economic sustainability of the current fisheries policy in Thailand.